(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The main objective of this paper is to analyze therecent past trends and patterns of urbanization, urban economic growth, andurban equity measured by urban poverty and inequality in India. Inaddition, it reviews the different urban development policies and programmeswhich are undertaken in different Plan Periods in India. The analysis shows thathigher rate of urbanization is associated with higher economic growth, lowerlevel of poverty and higher extent of inequality in urban India. Finally,the study suggests that Indian government needs to speed up the urbanizationrate as it contributes higher share of national GDP by reducing urban povertyand inequality.